ANATOMICAL CHARACTERISTICS OF THE RAT SPLEEN DURING THE INTRODUCTION OF A NON-GENETICALLY MODIFIED PRODUCT (Conferencea, 2021)
The results of the analysis of body weight changes in three-month-old white rats showed that the shape of the spleen acquires a crescent shape, located at the level of the 10th rib. The mass of animals of 3 months of age was on average 102.3 ± 4.2 g. The absolute mass of the organ is on average 0.3± 0.03 g. The mass index is on average 0.33±0.04%. The length of the spleen was on average 21.9±0.4 mm. The growth rate is 272.0%. The width of the spleen averaged 6.0±0.2 mm. The growth rate is 180.2%. The thickness of the spleen was on average 2.92±0.19 mm. The growth rate is equal to- 143.3%. The height of the spleen is on average 2.9 ± 0.2 mm. The area of the organ averaged 118.9±0.23 mm2 . The mass of 6-month-old animals was on average 168.8 ± 1.4g. The absolute mass of the organ is on average 0.8 ± 0.7 g. The mass index is on average 0.5 ± 0.04%. The mass of animals compared to 3-monthold rats increased by 1.47 times, and the absolute mass of the organ by 1.52 times.